CARÁNGANO AND WOMEN: STORY OF AN INSTRUMENT THREATENED WITH EXTINCTION - Trujillo, Andrea (International Library of African Music, 2019)
This article describes the results of an ethnomusicological study on the carángano, a ground bow instrument played only by women in the small villages of the Colombia Caribbean region. Before the introduction of electricity, the inhabitants contemplated the full moon as the women played, danced and laughed to the sound of this instrument. This instrument is now almost extinct. In this article, the social function, organological structure and repertoire of this instrument are analysed. The relationship between the carángano and other ground bows such as the tingo-talango or the dumbu-kalinga and sekituleghe on the American and African continents is discussed. These musical practices require urgent attention since they harbour musical and identification values belonging to the Colombian Caribbean region while sharing cultural aspects which connect Africans and African descendants across vast distances.
Keywords: Women; Musical instruments; Intangible Cultural Heritage; Colombian Caribbean Region; Carángano (Instrument); Ground Bow; Trans-Atlantic; African Music